Iloprost infusion prevents the insulin‐induced reduction in skeletal muscle microvascular blood volume but does not enhance peripheral glucose uptake in type 2 diabetic patients. Issue 11 (27th July 2018) - Emanuel, Anna L.; de Clercq, Nicolien C.; Koopen, Annefleur M.; van Poelgeest, Erik; Serlie, Mireille J. M.; van Raalte, Daniel H.; Kramer, Mark H. H.; Nieuwdorp, Max; Eringa, Etto C.; Serné, Erik H.
Abstract : Aims: In type 2 diabetes impaired insulin‐induced muscle perfusion is thought to contribute to reduced whole‐body glucose uptake. In this study, we examined the effects of iloprost, a stable prostacyclin analogue, on insulin‐induced muscle capillary recruitment and whole‐body glucose uptake. Materials and Methods: In a randomized cross‐over design, 12 type 2 diabetes patients (age, 55 [46‐69] years; BMI, 33.1 [31.0‐39] kg/m 2 ) underwent two hyperinsulinaemic‐euglycaemic clamps, one with and one without simultaneous low‐dose iloprost infusion. Contrast‐enhanced ultrasonography of the vastus lateralis muscle was performed before and during the clamp. Muscle capillary recruitment was calculated as percentage change in microvascular blood volume (MBV) before and during the clamp. Results: Insulin infusion reduced skeletal muscle MBV by ~50% compared to the fasting state (fasting, 1.77·10 −4 [1.54·10 −5 –2.44·10 −3 ] arbitrary units (AU); hyperinsulinaemia, 6.69·10 −5 [2.68·10 −6 –5.72·10 −4 ] AU; P  = 0.050). Infusion of iloprost prevented this insulin‐induced skeletal muscle capillary derecruitment, from (−49.5 [−89.5 to 55.3] %) to (8.0 [−68.8 to 306.6] %), for conditions without and with iloprost, respectively. The rate of glucose disappearance (Rd ) did not change significantly during iloprost infusion (17.3 [10.0‐40.8] μmol/kg/min) compared with insulin infusion alone (17.6 [9.9‐68.7] μmol/kg/min). Conclusions: Our data suggest that acute improvement in insulin‐stimulated muscle perfusion is not an attractive therapeutic approach to bypass cellular resistance to glucose uptake in type 2 diabetes. Whether long‐term improvements in insulin‐induced muscle perfusion may prove beneficial for glucose disposal remains to be determined.